Situational Crime Prevention Dalam Kejahatan Pencurian Kelapa Sawit di PT Bintara Tani Nusantara, Sumatera Barat - Margaret, Monica; Puspita, Febiana Indah (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
This article discusses crime prevention strategies with a situational approach in palm oil theft atPT Bintara Tani Nusantara (BTN). Situational Crime Prevention theory focuses on theopportunity, the place or context in which the crime is committed, and the target of the crime. Thisanalysis explains the factors of palm oil theft in PT BTN's plantation then the application of crimeprevention strategies in security implemented by PT BTN. The method used in this research isdescriptive qualitative research method. The research was conducted in the plantation of PT BTNSungai Beremas Sub-district and was conducted within five months. This research obtained datafrom three sources. The first source is an Indonesian Sustainable Palm Oil System (ISPO) staff atPT BTN, then the second source is PT BTN plantation security, and the last source is a formerconvict of palm oil theft at PT BTN. The results of this study show that the security measuresimplemented by PT BTN in guarding the plantation area include guard posts, barrier portal, ditchessurrounding the plantation area and roving security guards who conduct surveillance by walkingaround the PT BTN plantation area.